Studi Tentang Work Life Balance dan Kepuasan Karir Pekerja Wanita di Jakarta [A Study of Work-Life Balance and Career Satisfaction of Working Women in Jakarta] - Sylvia Diana Purba; Levi Nilawati (Universitas Pelita Harapan, 2015)
This research proposes to find out the influence of availability of career information on career satisfaction of career woman in Jakarta, Participants in this study are 199 women, consist of lecturers, doctors, police women, bank employees, etc. Work-life balance, awareness of organizational plans for self, and match between individual and organizational career plans are used as mediating variables on the impact of availability of career information toward career satisfaction. Research finding shows that work-life balance and awareness of organizational plans have no significant effects as mediating variables on the impact of the availability of career information toward career satisfaction. Meanwhile, the match between individual and organizational career plans have a significant effect as a weak mediating variable. Work-life balance issues seem not to be a concern informing career satisfaction among career women in Indonesia.